2021
DOI: 10.3233/jifs-202503
|View full text |Cite
|
Sign up to set email alerts
|

Big data reliability: A critical review

Abstract: Big data requires new technologies and tools to process, analyze and interpret the vast amount of high-speed heterogeneous information. A simple mistake in processing software, error in data, and malfunctioning in hardware results in inaccurate analysis, compromised results, and inadequate performance. Thus, measures concerning reliability play an important role in determining the quality of Big data. Literature related to Big data software reliability was critically examined in this paper to investigate: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Kaswan et al [11] suggested a student success prediction method used the WEKA Naive Bayes method for building prediction models. Six properties have been tested: income households, university, ethnicity, gender, home town and CGPA.…”
Section: Literature Surveymentioning
confidence: 99%
“…Kaswan et al [11] suggested a student success prediction method used the WEKA Naive Bayes method for building prediction models. Six properties have been tested: income households, university, ethnicity, gender, home town and CGPA.…”
Section: Literature Surveymentioning
confidence: 99%
“…Data integration is a little more involved, as it entails making the data useful and common throughout the process. Usually, data ingestion, cleansing, and standardization integrate the data into the process (Sharma, Kumar and Kaswan, 2021;. Data integration has five parameters:…”
Section: Parameters Identification Of Data Integrationmentioning
confidence: 99%